Pengaruh Financing to Deposit Ratio dan Non Performing Financing Terhadap Return on Assets dengan Capital Adequacy Ratio Sebagai Variabel Intervening pada Perbankan Syariah di Indonesia pada Tahun 2017-2021 - Ramayani; Nur Ahmadi Bi Rahmani; Nurul Jannah (Economic Reviews Journal, 2024)
This study aims to determine the Effect of Financing to Deposit Ratio and Non-Performing Financing on Return on Assets with Capital Adequacy Ratio as Intervening Variables in Islamic Banking in Indonesia in 2017-2021. This study uses a quantitative approach method and uses secondary data, namely quarterly financial ratio reports of banks registered with OJK from 2017-2021. The analysis technique used is a partial test (t test), simultaneous test (F test), Coefficient of Determination test (R2 test) and path analysis test. The results of this study indicate (1) Financing to Deposit Ratio (FDR) has an effect on Return on Assets (ROA), (2) Non Performing Financing (NPF) has an effect on Return on Assets (ROA), (3) Financing to Deposit Ratio (FDR) ) has no effect on Capital Adequacy Ratio (CAR) (4) Non Performing Financing (NPF) has an effect on Capital Adequacy Ratio (CAR), (5) Capital Adequacy Ratio (CAR) can mediate the effect of Financing to Deposit Ratio (FDR) on Return On Assets (ROA), and (6) Capital Adequacy Ratio (CAR) cannot mediate the effect of Non Performing Financing (NPF) on Return On Assets (ROA).